Comportamento informacional de pós-graduandos de educação: estudo sobre as variáveis intervenientes - Oliveira, Etiene Siqueira de [UNESP] (2013)
Studies on information behavior permit identify individual’s conduct, how is the information seeking process and the finality of information use. Considering the above the main purpose of this study is to investigate the relationship between personality and information behavior of graduate students in Engineering from area III of CAPES more specifically the Production, Mechanical, Aerospace and Naval and Oceanic Engineering. The specific purposes are to characterize the information behavior of graduate students, to verify the existence of significant difference between the information behavior of masters and doctoral students, to compare the information behavior presented by graduate students of the four sub fields of Engineering that comprise this research, to identify the personality of graduate students through the scale of 50 items, and to associate the personality traits to the information behavior of graduate students. For the identification of personality was used the assumption in the area of Psychology the Theory of Personality Traits which presents the Big Five model. As an instrument of data collection, a web-based questionnaire was used, as well as the Personality Scale 50 items Goldberg. For data analysis we used the statistical software SPSS to check the relationship between the variables. The results indicate mainly the graduate students actively seek information, but does not use the passive search for information. They have difficulties in interacting with the databases and do not use keywords and Boolean operators. Despite the difficulties of using bases, it was found that most part of the students received some sort of guidance for using the bases. The resources most used were scientific journals, books and theses and dissertations. It was observed that the personality trait prevalent in participants was the conscientiousness... (Complete abstract click electronic access below)